A BIBLIOMETRIC MAPPING OF RESEARCH TRENDS AND DIRECTIONS ON THE RELATIONSHIP BETWEEN INFRASTRUCTURE AND RURAL DEVELOPMENT - Popa, Marius George; Sima, Violeta; Andrei, Jean Vasile (Economics of Agriculture, 2025)
This paper explores how infrastructure is connected to rural development by analysing trends in academic research over the past three decades. Infrastructure is essential for improving the quality of life and supporting economic growth in rural areas. As rural regions often face challenges like isolation, limited services and population decline, developing adequate infrastructure is seen as a key solution. To better understand how this topic has been studied, the research uses a bibliometric method based on articles indexed in the Web of Science™ Core Collection. A total of 166 publications from 1993 to 2025 were analysed using the VOSviewer software. Three main clusters were identified: Socio-political dimensions of rural infrastructure, Sustainable transformation and rural development, Economic performance and public infrastructure. The paper highlights the increasing international interest in these topics, with strong contributions from countries like China, the United States and Romania, but still international collaboration remains modest.